Togo : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1999)
This Selected Issues paper on Togo examines the banking sector in Togo. It describes the nature of the problems presently confronting the Togolese banking system, most of which have their origins in the impact of the sociopolitical crisis of 1991-93 on the banks' portfolio structure and profitability. The paper analyzes these vulnerabilities, and the reform perspectives for the financial sector. The paper highlights that the decline in revenue as a share of GDP raises the question of whether the current tax structure has been fully exploited.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet